Evaluasi Usabilitas SIKAPTA Jurusan Teknik Industri UNS Menggunakan Hierarchical Task Analysis - Iftadi, Irwan; Priyandari, Yusuf; Cahyaningrum, Fransiska Endah (Performa: Media Ilmiah Teknik Industri, 2012)
SIKAPTA is a computer based information system owned by department of industrial engineering, Sebelas Maret University (UNS). SIKAPTA is designed to manage course activities, specifically for Kerja Praktek and Tugas Akhir subject. SIKAPTA has not been evaluated since SIKPATA implementation, so it is important to evaluate specifically for usability problems. This research uses Hierarchical Task Analysis (HTA) approach in order to generate structured tasks for each user while they use SIKPATA and then uses the HTA of SIKAPTA as a bases to evaluate the usability of SIKAPTA. In addition to HTA, an usability guideline was developed and used to help SIKAPTA’s users to find the usability problems while they use SIKAPTA. The evaluation of SIKAPTA involved three kinds of user, they are administrator staff, students, and coordinator of Tugas Akhir. The result of this research shows that a mapping of users’s tasks using HTA can facilitate in conducting usability evaluations in detail for each application interface used for a task. In addition to that, the evaluation of SIKAPTA shows that there are 31 complaints said by users, which consists of 4 complaints from administrator, 13 complaints from student, and 14 complaints from coordinator of Tugas Akhir. The complaints represent usability problems and they are distributed in 3, 15 and 12 tasks for administrator, student, and coordinator of Tugas Akhir respectively.